The Process of Meaning Creation: A semiotic Analysis of Facebook Posts of English Works! - Parveen, Sabahat; Ikhtiar, Anam (Pakistan Languages and Humanities Review, 2023)
Facebook posts are strategically created to achieve commercial objectives, encompassing digital advertising, content promotion, and audience engagement. A specific case in point involves the analysis of posts on the English Works! social media page. The study draws upon Kress and Leeuwen’s concept of Multimodality of signs to analyze these visual cues. The findings indicate that each image serves as a sign, conveying insights about the program's essence, updates, events, and activities to the audience. The color palettes used in these images play a pivotal role in establishing the program's agenda and thematic representation. The connotations embedded in the Facebook posts predominantly revolve around themes of learning, unity, celebration, empowerment, success, and recognition. These connotations are intricately tied to the journey of English Works! students. Future researchers could extend the application of semiotics to other forms of visual communication media, such as art photography, banners, and printed advertisements.